2016
DOI: 10.1016/j.jbiomech.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modeling of stress softening and permanent set in a porcine skin tissue: Impact of the storage preservation

Abstract: Prior to testing, soft tissues are usually maintained in different media and additives (solution, air, cryopreservant…) under various environment conditions (temperature, storage duration….). In many cases, results from mechanical tests performed on these stored tissues are supposed to be as closed as possible to the fresh ones. In the present work, cyclic tensile tests were performed with increasing values of strain on porcine skin tissues (excised following the Langer's lines) to enhance tissues mechanical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The data obtained from the breast skin specimens are consistent with the behavior of skin that has been reported earlier in the literature (Abas and Barbenel, 1982; Dunn et al 1985, Clark et al, 1996; Edsberg et al 1999; Bischoff et al, 2000; Annaidh et al, 2012; Caro-Betelle et al 2016 and others). This data has significant patient-specific variability and contains data on the influence of specimen storage on the mechanical response.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The data obtained from the breast skin specimens are consistent with the behavior of skin that has been reported earlier in the literature (Abas and Barbenel, 1982; Dunn et al 1985, Clark et al, 1996; Edsberg et al 1999; Bischoff et al, 2000; Annaidh et al, 2012; Caro-Betelle et al 2016 and others). This data has significant patient-specific variability and contains data on the influence of specimen storage on the mechanical response.…”
Section: Resultssupporting
confidence: 90%
“…The microstructure and biomechanical properties of skin (and other soft biological tissues) have been studied by numerous investigators, and there exists a common understanding of both (see for example, Gibson et al, 1965; Fung, 1967; Harkness, 1971; Wilkes et al, 1973; Sanders and Goldstein, 1995; Annaidh, 2012: Menon 2012; Tonge et al 2013a,b; Caro-Bretelle et al, 2015, 2016; Bancelin et al, 2015). A succinct summary of skin composition is provided by Sanders and Goldstein (1995): skin is composed of collagen (27 to 39% by volume, 75 to 80% of fat-free dry weight), elastin (0.2 to 0.6% by volume, 4% of fat-free dry weight), glycosaminoglycans (0.03 to 0.35% by volume), and water (60 to 72% by volume).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically with respect to skin, Foultz (Foutz et al, 1992) tested rat skin specimens and concluded that "freezing did not affect the resistance of the skin to tensile deformation". More recently, Caro-Betellene et al (Caro-Bretelle et al, 2016 examined different preservation methods and concluded that cryopreservation following a specific protocol is the only way to maintain the mechanical behavior of fresh samples of porcine skin. Ranamukhaarachchi et al (2016) compared fresh and frozen porcine and human skin specimens, under conditions of microindentation and microneedle insertion and found significant influence of freezing.…”
Section: Introductionmentioning
confidence: 99%